Electrochemical Dearomative Spirocyclization. Issue 9 (27th March 2023) - Li, Nan; Shi, Zhaojiang; Wang, Wei‐Zhen; Yuan, Yaofeng; Ye, Ke‐Yin
Abstract: Electrochemical dearomative spirocyclization serves as a green and sustainable approach to convert the flat, two‐dimension aromatic feedstock into the value‐added three‐dimension spirocyclic architectures. This review highlights the recent advances, emphasizes mechanistic discussions, and showcases synthetic applications of this emerging versatile and powerful transformation. Abstract : Recent advances in electrochemical dearomative spirocyclization, including reaction development, mechanistic investigations, and synthetic applications, are highlighted.